INTEGRATING MICROSOFT IMMERSIVE READER IN SMAR MODEL TO PROMOTE STUDENTS’ READING COMPREHENSION - Septi Riana Dewi; Soraya Fatmawati; Anang Widodo (Universitas Muria Kudus, 2021)
The use of technology has become more inseparable as a part of the learning process in and out of the class. It offers various new tools that can be utilized by both learners and teachers. Microsoft Immersive Reader (MIR) is one of learning tools which equipped with various features to help students reading comprehension. In addition, to assist teacher in using technology in classroom, SMAR model serves as a framework which allows the teacher to assess their use of technology and determine the level of technology integration in their classroom. This study focuses on how to utilize MIR with SMAR model in reading class. The study was conducted at English Education Department. There were 1 lecturer and 35 students of the second semester who took part as repsondents. The data were gathered from observation and interview. The result shows that the lecturer gives psotive view that MIR will improve the quality of teaching and learning and also improve students’ motivation in learning reading. The students viewed the use MIR as motivating, and various features on MIR enabled them to understand the assigned reading topic much easier. Moreover, the reading assignment incorporating the use of MIR features encouraged them to actively participate in reading activities in a collaborative atmoshphere.